PARADIGMA TAFSIR MAQASIDI - Sutrisno, Sutrisno (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
This article discusses the concept of maqasid-based interpretation known as al-tafsir al-maqashidi. This type of interpretation is one of the new breakthroughs of contemporary scholars in facing various limitations of existing interpretive methods. This method is built from the concept of maqasid which was only limited to doctrine, then developed into a method or paradigm of thinking and religion. This literary study, based on biblical studies, seeks to discover the construction of the maqasidi commentary by emphasizing the formulation of specific methods of interpreting the Qur’an. Disclosure of the deepest meaning (maqasid) of the Qur’an in order to succeed the mission of the Qur’an as a book of guidance that can provide solutions to the humanitarian problem that continues to grow allegedly became the hallmark of this model of tafsir.